2008
DOI: 10.1016/j.advwatres.2008.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of the logarithmic layer of double-averaged streamwise velocity profiles in gravel-bed river flows

Abstract: a b s t r a c tThe logarithmic layer of double-averaged (in time and space) streamwise velocity profiles obtained from field measurements made in the Swiss rivers, Venoge and Chamberonne is parameterized and discussed. Velocity measurements were made using a 3D Acoustic Doppler Velocity Profiler. Both riverbeds are hydraulically rough, composed of coarse gravel, with relative submergences (h/D 50 ) of 5.25 and 5.96, respectively. From the observations, the flow may be divided into three different layers: a rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 35 publications
(48 reference statements)
2
48
0
Order By: Relevance
“…In many instances of open-channel flow, it was found that a logarithmic law can describe the velocity profile in the bottom 15% of the flow depth [18], 20% [19], 50% [20] or 75% [13]. Thus there is not an explicit standard for the flow heights on the estimation of u*, d and z0 using a fitted logarithmic profile.…”
Section: Methods To Calculate D and Z 0 From A Given Velocity Profilementioning
confidence: 99%
See 1 more Smart Citation
“…In many instances of open-channel flow, it was found that a logarithmic law can describe the velocity profile in the bottom 15% of the flow depth [18], 20% [19], 50% [20] or 75% [13]. Thus there is not an explicit standard for the flow heights on the estimation of u*, d and z0 using a fitted logarithmic profile.…”
Section: Methods To Calculate D and Z 0 From A Given Velocity Profilementioning
confidence: 99%
“…At the step edges, the vertical velocity distribution in the turbulent boundary layer can be approximated by a power law [8][9][10][11], and data obtained in bed-roughened flows show that there is a region above the roughness layer where the smooth boundary upstream of the steps still adequately describes the vertical velocity distribution [12][13][14]. This transition boundary layer will be used to investigate and characterize the roughness parameters and the development of turbulent boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…Finnigan, Shaw, & Patton, 2009;Raupach & Shaw, 1982). In recent years, it has also been successfully employed for studies of open-channel flows over fixed rough beds, examples of which are given in Nikora and Rowiński (2008), Franca, Ferreira, and Lemmin (2008), Mignot, Barthelemy, andHurther (2009), Ferreira, Ferreira, Ricardo, andFranca (2010), Yuan and Piomelli (2014). Among other findings, these studies highlight the potential importance of additional (dispersive) fluid stresses, which appear due to roughness effects that introduce local heterogeneities in the time-averaged flow.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis and modeling of heterogeneous and irregular-bounded open-channel flows by means of double-averaging (DA) methods is presented by several authors for different problems in fluvial hydraulics (Aberle and Koll 2004;Manes et al 2007;Franca et al 2008;Stoesser and Nikora 2008;Ferreira et al 2010, among others). Franca et al (2010) and Mignot et al (2009) Recently, a journal's special issue on the application of the double-averaging approach to rough-bed flows was published (cf.…”
Section: Homogeneous and Heterogeneous Flowsmentioning
confidence: 99%